E3 Ubiquitin Ligases as Immunotherapeutic Target in Atherosclerotic Cardiovascular Disease - Poels, Kikkie; Vos, Winnie G.; Lutgens, Esther; Seijkens, Tom T. P. (Frontiers in Cardiovascular Medicine, 2020)
Chronic low-grade inflammation drives atherosclerosis and despite optimal pharmacological treatment of classical cardiovascular risk factors, one third of the patients with atherosclerotic cardiovascular disease has elevated inflammatory biomarkers. Additional anti-inflammatory strategies to target this residual inflammatory cardiovascular risk are therefore required. T-cells are a dominant cell type in human atherosclerotic lesions. Modulation of T-cell activation is therefore a potential strategy to target inflammation in atherosclerosis. Ubiquitination is an important regulatory mechanism of T-cell activation and several E3 ubiquitin ligases, including casitas B-lineage lymphoma proto-oncogene B (Cbl-B), itchy homolog (Itch), and gene related to anergy in lymphocytes (GRAIL), function as a natural brake on T-cell activation. In this review we discuss recent insights on the role of Cbl-B, Itch, and GRAIL in atherosclerosis and explore the therapeutic potential of these E3 ubiquitin ligases in cardiovascular medicine.